The Strategic Elements and Performance of Chinese Publicly Listed Automotive Manufacturers: A Proposed Conceptual Framework - Fu, Shanliang; Ng, Alex, Hou Hong; Lim, Kim Yew; Wong, Chee Hoo (INTI International University, 2019)
Automotive industry plays an important role in a nation’s economy and society. The automotive manufacturers are the main force of the automotive industry. The core research objectives of this study are the strategic elements of Chinese publicly listed automotive manufacturers experiencing a huge transformation progression under turbulent environmental changes. This study aims to focus on the relationship of competitive strategies, organizational innovation, positioning and performance of Chinese publicly listed automotive manufacturers. This study also works out a conceptual framework based on the four variables mentioned. The data is collected either from annual reports of Chinese automotive manufacturers, or from questionnaire distributed to managers at various level of these manufacturers. This study is to help Chinese automotive manufacturers survive and develop well by offering the results of this research on competitive strategy under the circumstance of current new technology trends.